Caetanoel: educação sentimental no mundo das canções - Andrade, Ênio Bernardes de (2023)
This research has as its object the study of intertextual dialogues between the song work of Caetano Veloso and the songbook of Noel Rosa, seeking to investigate the uniqueness of this case, established in Veloso's sentimental education which developments oscillate between celebration and conflict. About the relationship between the two songwriters, broader themes are discussed, such as the song formatting process in Brazil associated with media recordings, the development of a lyric characteristic of the song field and the presence of songs recorded in the individual and collective lives of different generations, since the 1930s, starting to compose their identities and affective memories. The concept of “sentimental education” is taken from José Miguel Wisnik (2004), understanding the song disseminated in the media as a “poetic-musical knowledge”, that in the case of Caetano Veloso, encompasses the presence of Noel Rosa in the auditory world of his childhood in Santo Amaro, on the radio and records, in his mother's voice, in his father's reflections, in his sister Maria Bethânia's singing and in his own voice. Comparative analyzes are proposed between songs by the two authors, starting from dialogues established by Caetano Veloso with Noel Rosa through intertextual games, in derivations, parodies, collages, appropriations and responses, as in the case of the emblematic song-manifest “Tropicália” (1968), created from Noel’s samba “São Coisas Nossas” (1932). The connection between Veloso and Rosa, even when they are in conflict, points to a way of being common to both, each in their own time, built their trajectories in a manner that was out of step with established social and aesthetic standards. Based on the song analyses, the idea is discussed that by repeatedly dialoguing with Noel Rosa, Caetano Veloso points to a critical view of the tradition that formed him through movements built from within the song series itself, updating it, expanding it, confronting it, transgressing it, treating it as a force present in the “synchronous-diachronic” perspective of a “transtemporal tradition”, according to the meaning of Campos (2006). The comparative methodology used integrates poetic, musical, intonation, performance and phonographic constructions, encompassing the interaction between lyrics, melody, vocal and corporal performance, harmony and instrumental arrangements, sound constructions in the studio, album covers, situation of the tracks in the context of the albums, intertexts with the song series and with other languages. The theoretical framework draws on, among other authors, Caetano Veloso's performance as an artist-critic, the semiotic concepts of Tatit (1996), researches about song and samba by Wisnik (2004), Campos (1974), Máximo and Didier (1990) and Sandroni (2012), studies on vocality by Zumthor (2010) and Cavarero (2011), intermediality and intertextuality by Compagnon (1996) and Hutcheon (1995), tradition and transgression by Campos (2006) and Foucault (2009).